Analisis Geomorfologi pada Daerah Kinal dan Sekitarnya, Kabupaten Kaur, Provinsi Bengkulu - Ugi Kurnia Gusti; Alfaris Hadi Pramana; Edy Sutriyono (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The Kinal area and its surroundings in Kaur Regency, Bengkulu Province, are geomorphologically influenced by regional tectonic activity associated with the Bukit Barisan structural system and sedimentary formations of the Lemau Formation. These regional geological conditions control the development of structural, fluvial, karst, and denudational landforms in the study area. The purpose of this study is to analyze the geomorphological characteristics of the Kinal area based on the genetic landform classification of Van Zuidam (1985). The research method applies a geomorphological approach consisting of morphographic, morphometric, and morphogenetic analyses using DEMNas and SRTM data supported by field verification. Landform classification was conducted genetically through interpretation of slope classes, elevation, drainage patterns, lithology, and geomorphic processes. The results indicate six main geomorphic units, namely structural fault ridges, alluvial plains, channel bars, karst hills, weakly dissected denudational hills, and strongly dissected denudational hills, with elevations ranging from 150 to 450 meters above sea level. Drainage patterns are predominantly dendritic and sub-dendritic, reflecting lithological variation and structural control under intensive denudational processes. These findings demonstrate that regional tectonics and lithological resistance play a significant role in controlling geomorphic evolution and landscape development in the Kinal area.